Tectonic Juxtaposition of Two Independent Paleoproterozoic Arcs by Cenozoic Duplexing in the Arun Tectonic Window of the Eastern Nepalese Himalaya - Li, Rui; Ao, Songjian; Xiao, Wenjiao; Schulmann, Karel; Mao, Qigui; Song, Dongfang; Tan, Zhou; Wang, Hao; Bhandari, Saunak (Frontiers in Earth Science, 2022)
The tectonic evolution of the Himalayan orogenic belt before Cenozoic convergence is important to understand its modern structural framework. There is still controversy regarding the tectonic history of the lower Lesser Himalaya Sequence (LHS) in the frame of Paleoproterozoic geological record. In this study, integrated analysis of field geology, zircon U-Pb age, Hf isotope and whole rock geochemistry were conducted across the LHS and Main Central Thrust zone in the Arun Valley, eastern Nepal, to address their Precambrian tectonic evolution and the later convergence. Two groups of metasedimentary rocks with different age spectrum of detrital zircons and Hf isotope in the Paleoproterozoic can be distinguished in an imbricated duplexing system in the study area. One group with a maximum depositional age around ca. 1800 Ma has a unimodal detrital zircon pattern and negative zircon ƐHf(t) values ranging from -8.9 to 0.9. These data can be interpreted to reflect the deposition of zircons close to a Japanese-type arc that was isolated from the northern Indian Craton. The other group of calc-silicate rocks and quartzite with a multiple peak of detrital zircons in the Paleoproterozoic show a younger maximum depositional age around ca. 1600 Ma and variable zircon ƐHf(t) values ranging from -6.7 to 8.8, indicating their deposition in a back-arc basin of an Andean-type arc established on the northern Indian Craton. The geochemistry of an orthogneiss sample dated at 1783 ± 11 Ma indicates a high potassium, peraluminous granodiorite protolith emplaced in a volcanic arc or syn-collisional tectonic setting, supporting the existence of the Paleoproterozoic Andean-type arc. We hypothesize that possibly two arc systems developed respectively onto and in the proximity of northern Indian Craton in Paleoproterozoic at the final stages of Columbia supercontinent formation. These two arcs were juxtaposed either in Paleoproterozoic or Cenozoic time and were finally imbricated during the Cenozoic duplexing.